pH, Calcium Ion Release, and Setting Time of an Experimental Mineral Trioxide Aggregate-based Root Canal Sealer - Massi, Santiago; Tanomaru-Filho, Mario [UNESP]; Silva, Guilherme Ferreira; Hungaro Duarte, Marco Antonio; Grizzo, Larissa Tercilia; Rabelo Buzalaf, Marilia Afonso; Guerreiro-Tanomaru, Juliane Maria (Elsevier B.V., 2011)
Introduction: An experimental mineral trioxide aggregate sealer (MTAS) has been developed for use as a root canal sealer. The aim of this study was to evaluate the setting time, pH, and calcium ion release of MTAS compared with white Portland cement (CPB-40; Votorantin Cimentos, Camargo Correa SA, Pedro Leopoldo, MG, Brazil), white MTA Angelus (MTA; Angelus, Londrina, PR, Brazil), and AH Plus (Dentsply DeTrey, Konstanz, Germany). Methods: For the evaluation of setting time, each material was analyzed using Gilmore-type needles. Polyethylene tubes with the materials were immersed in distilled water for the measurement of pH (digital pH meter) and calcium release (atomic absorption spectrophotometry). The evaluations were performed at 3, 6, 12, 24, and 48 hours and 7, 14, and 28 days. Data were analyzed by analysis of variance and the Tukey test at 5% significance level. Results: MTAS showed higher calcium release at all experimental periods, a greater increase in pH up to 48 hours and the longest setting time. Conclusions: MTAS presented favorable properties for its indication as a root canal sealer. (J Endod 2011;37:844-846)
Keywords: Endodontic sealer; mineral trioxide aggregate; physicochemical properties; Portland cement